"Historical‐Critical Ministry? The Biblical Studies Classroom as Restorative Secular Space". (29th November 2018) - Parks, Sara
Abstract: This article revisits the past decades of scholarly use (or rather non‐use) of Bernadette Brooten's Women Leaders in the Ancient Synagogue to reveal that citation practices in biblical studies—or any field—can be inherently political (e.g. misogynistic) whilst maintaining a pretence of scientific objectivity. As a corrective, the author calls for the abandonment of the myth of neutrality in the biblical studies classroom. She argues that rape is only one end of a long spectrum of behaviours that silence; at the other, more subtle end of that spectrum, and all along it, are thousands of lesser instances of silencing and diminishing that occur in the classroom, that are gentler extensions of the notion that women's bodies do not belong to them, that men are the default human beings, and that women are valuable only insofar as they are pleasing or useful from a male standpoint. Parks advocates a biblical studies pedagogy that intentionally upholds inclusion and diversity in its curriculum, its group dynamics, and its citation practices, even (or especially) within institutions that do not. This is especially important given the prevalence of survivors of sexual assault and gender‐based violence in every classroom; maintaining a neutral stance implicitly re‐inscribes and encourages the status quo of rape culture.